Locomotor disability in very elderly people: value of a programme for screening and provision of aids for daily living. Issue 6745 (28th July 1990) - Hart, D; Bowling, A; Ellis, M; Silman, A
Abstract : OBJECTIVE–To assess the prevalence of potentially reversible locomotor disabilities in elderly subjects and the cost effectiveness of providing aids for daily living. DESIGN–Population based randomised controlled trial of subjects aged greater than or equal to 85 living independently in an inner London borough. SETTING–21 Electoral wards of the London Borough of Hackney. SUBJECTS–1255 Subjects aged greater than or equal to 85 living in their own home whose names were obtained from general practitioner lists and cross checked against the electoral register, 511 of whom were subsequently found to be ineligible. Of the 744 remaining, those with disability on screening were randomised and allocated to an intervention group (36) or a control group (43), in which intervention was postponed until four weeks, after the follow up assessment. Subjects with aids supplied previously were excluded from the intervention phase. INTERVENTIONS–Provision of raised toilet seat, teapot tipper, tap turner, shoe horn and elastic laces, and double handled saucepan. MAIN OUTCOME MEASURES–Degree of difficulty (grades 1-4) with specific tasks (getting on and off a toilet, pouring from a teapot into a cup, turning taps on and off, carrying a saucepan of standard weight, and putting on shoes) and time taken to perform them. RESULTS–545 (73%) Of the 744 eligible subjects assessed; 428 had no disability and 118 had difficulty with at least one task. Some had had their disability recognised before the study and already had aids, representing half of those with difficulty getting on and off the toilet but 24% for putting on shoes and 13% for pouring from a teapot and turning on a tap. The mean number of difficulties was similar between the groups (intervention group 1.7, control group 1.6). Time taken to complete the tasks corresponded with the observed grade of difficulty. All aids were associated with reduced difficulty according to observer assessment (% improvement intervention group v control group: raised toilet seat, 71 v 13 teapot tipper 100 v 33; tap turner 100 v 0; saucepan 88 v 0; shoe horn 50 v 13) and time taken to complete the tasks. A cost benefit analysis of this screening-intervention programme suggested a total cost of 32 pounds per individual benefit. CONCLUSIONS–Appreciable degrees of unrecognised locomotor disability are detected on screening of very elderly people living independently. Providing aids offers a feasible and cost effective means of improving function in such people.